ACUTE RIGHT VENTRICULAR FAILURE - A. E. Bautin; V. V. Osovskikh (Вестник анестезиологии и реаниматологии, 2018)
From the beginning of this century, clinicians started to pay more attention to the right ventricular dysfunction. It is related to the thorough studying of pathologies, during which the right ventricular dysfunction plays the key role, such as pulmonary hypertension, congenital heart disorders, and thromboembolia of the pulmonary artery. Currently, it has been proved that acute right ventricular failure makes 3-9% of all acute heart failures, the hospital lethality in these clinical situations makes from 5 to 17%. The objective of the literature review is to provide anesthesiologists and emergency physicians with information on modern approaches to diagnostics and treatment of acute right ventricular failure.The review presents data on normal anatomy and physiology of the right ventricle, morphological and functional changes when various forms of acute right ventricular failure develop. Diagnostics and comprehensive intensive care are described for the two most frequent types of acute right ventricular failure, which are reduction of right ventricular contractility and its overloading with afterload.